QUALITY CONTROL ANALYSIS USING STATISTICAL QUALITY CONTROL AT PT MASSINDO SINAR PRATAMA MANADO - Runtuwene, Vayska Eliana; Massie, James D.D; Tumewu, Ferdinand . (Universitas Sam Ratulangi, 2017)
Abstract: In order to survive in a competitive market, improving quality and productivity of product or process is a must for any company. This study is about to apply the statistical quality control tools in the production processing and on final product in order to reduce defects by identifying where the highest waste is occur at and to give suggestion for improvement. The approach used in this study is direct observation, thorough examination of production process lines, fishbone diagram, and information has been collected from company through interview, and control chart (p-chart) was constructed. It has been found that the company has good quality control but still found the defect product. The principal aim of the study is to create awareness to quality team how to use statistical tools in the problem analysis, especially to train quality team on how to held an effective brainstorming session, and exploit these data in cause-and-effect diagram construction and control chart construction.Keywords: quality, statistical quality control, ishikawa diagram, p-control chart